Pan-Africanism and Economic Nationalism: W. E. B. Du Bois's Black Reconstruction and the Failings of the "Black Marxism" Thesis. (November 2017) - Anderson, Patrick
In recent decades, it has become popular to read the later work of W. E. B. Du Bois through a Marxist lens. Not only is Du Bois often considered a participant in the Marxist tradition, his historiographical masterpiece Black Reconstruction is often offered up as evidence for such arguments. Here, I challenge those who have attempted to interpret Du Bois as a Marxist by situating his work in relation to the Pan-African tradition to which he dedicated decades of his life. Du Bois's views on Reconstruction and economics are shaped by Pan-African ideas, not Marxist theory, and his theoretical and practical confrontations with both his White and Black Marxist contemporaries reveals the distance between his Pan-Africanism and their Marxism. Contrary to the prevailing interpretations, Du Bois's Black Reconstruction is not a Marxist text but a Pan-Africanist argument against Marxism's inability to account for the structure of modern European Empire.